2023
DOI: 10.1177/00315125231178067
|View full text |Cite
|
Sign up to set email alerts
|

Listening to Preferred and Loud Music Enhances Taekwondo Physical Performances in Adolescent Athletes

Ibrahim Ouergui,
Eya Jebabli,
Slaheddine Delleli
et al.

Abstract: In this study, we aimed to investigate the effects of warm-up music preference and loudness on physical performance, perceived exertion (RPE), and enjoyment in young taekwondo athletes. In a crossover counterbalanced design, 20 taekwondo athletes (10 male, 10 female) performed a battery of physical tasks specific to taekwondo under the following five conditions: (a) No music (NM), (b) Preferred music-Soft (60 dB; PMS), (c) Preferred music-Loud (80 dB; PML), (d) Non-preferred music-Soft (60 dB; NPMS), and (e) N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This stage of life, commonly known as adolescence, is viewed as a crucial period for psychological, social, and cognitive development; the role of music within this framework is significant. As per the research conducted by Ouergui et al (2023) , youth display a high frequency of interaction and deep engagement with music. In the contemporary digital age, music is ubiquitous.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…This stage of life, commonly known as adolescence, is viewed as a crucial period for psychological, social, and cognitive development; the role of music within this framework is significant. As per the research conducted by Ouergui et al (2023) , youth display a high frequency of interaction and deep engagement with music. In the contemporary digital age, music is ubiquitous.…”
Section: Introductionmentioning
confidence: 78%
“…Esthetic studies illustrate that music can trigger profound emotional experiences and spiritual exchanges and offer beauty appreciation. Education research suggests that music education can enhance holistic adolescent development, including intellectual, emotional, social, and moral dimensions ( Ouergui et al, 2023 ). Thus, we should motivate teenagers to choose music of high esthetic and educational value, including classical music, ethnic music, and world music.…”
Section: Implementing Effective Coping Strategiesmentioning
confidence: 99%
“…Therefore, the reported results generated by their combination are not surprising, since the physical abilities and psychological aspects are interrelated and affect each other ( 27 ). In fact, under preferred conditions, warm-up music may increase the anticipatory response to exercise ( 25 ), resulting in increased effort and muscular force development ( 19 , 20 ). In this consideration, listening to music during a warm-up session has been shown to increase plasma catecholamine concentrations, which may promote muscular activation, shift blood flow toward skeletal muscles, and modify metabolic reactions during afterward exercise ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…In combat sports, evidences regarding potential benefits from listening to warm-up music are limited. In TKD, research has revealed that warm-up music improves performances and reduced fatigue index during specific tasks ( 24 , 25 ), with greater benefits using preferred than non-preferred music ( 25 ). Moreover, tempo of the listened music has been reported to modulate music motivational quality ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation